Les Township tours au KwaZulu-Natal (Afrique du Sud) : d’une réappropriation historique et identitaire à l’avènement d’un socio-tourisme - Fabrice Folio (EchoGéo)
Processes of identity and historical appropriation, rooted in economic purpose, are today arising in South Africa. A tourism activity, based on authenticity and interaction, becomes particularly popular: the Township tours. It assumes an episode of the country history, i.e. urban segregation, which was given a lot of media coverage. In the meantime, it tries to invert the repulsive image that is commonly associated with apartheid. The attraction for township areas has to be linked to the wish of understanding the institutionalized racial discrimination in South Africa, as well as its pacific end. Paradoxically, the reputation of dangerousness, poverty and informality of those former black urban areas seems to act as a loss leader. Through the example of the province of KwaZulu-Natal, it will be seen that this new socio-tourist activity is now playing a multiculturalism card carried by popular icons, with the local development target in the background.